Müller glia phagocytose dead photoreceptor cells in a mouse model of retinal degenerative disease - Sakami, Sanae (FASEB J, 2019)
Retinitis pigmentosa is a devastating, blinding disorder that affects 1 in 4000 people worldwide. During the progression of the disorder, phagocytic clearance of dead photoreceptor cell bodies has a protective role by preventing additional retinal damage from accumulation of cellular debris. However, the cells responsible for the clearance remain unidentified. Taking advantage of a mouse model of retinitis pigmentosa (Rho(P23H/P23H)), we clarified the roles of Müller glia in the phagocytosis of rod photoreceptor cells. During the early stage of retinal degeneration, Müller glial cells participated in the phagocytosis of dying or dead rod photoreceptors throughout the outer nuclear layer. Nearly 50% of Müller glia engaged in phagocytosis. Among the Müller phagosomes, >90% matured into phagolysosomes. Those observations indicated that Müller glial cells are the primary contributor to phagocytosis. In contrast, macrophages migrate to the inner part of the outer nuclear layer during photoreceptor degeneration, participating in the phagocytosis of a limited population of dying or dead photoreceptor cells. In healthy retinas of wild-type mice, Müller glial cells phagocytosed cell bodies of dead rod photoreceptors albeit at a lower frequency. Taken together, the phagocytic function of Müller glia is responsible for retinal homeostasis and reorganization under normal and pathologic conditions.—Sakami, S., Imanishi, Y., Palczewski, K. Müller glia phagocytose dead photoreceptor cells in a mouse model of retinal degenerative disease.